(untitled) (Journal of Medical & Health Sciences Review, 2025)
The accumulation of augmented reality (AR) and virtual reality (VR) in radiology is transforming procedural planning, medical imaging, and diagnostics. These state of art technologies offer immersive and interactive experiences, enhancing precision in interventional radiology, medical education, and surgical planning. AR aids with vascular intervention, tumor localization, and precise medicine by overlaying imaging data onto the patient’s body in real-time. Virtual reality (VR) offers 3D holographic recreation of complicated anatomical structures to enhance medical training and diagnostic precision. Despite of proficient benefits of AR and VR there are many drawbacks of their usage in radiology, for example hindrances in the smooth integration with current workflows, high installation costs, and hardware problems. As AR is best suited for real-time procedural guidance, in contrary VR is excellent for education and in-depth image analysis. AR/VR both could be efficient in reducing diagnostic errors, refining strategies for surgeries, and patient outcomes. For amplifying the usage of AR/VR in clinical applications there is need of development in AI integration, user-friendly designs, and cost-effective solutions. To authenticate long term benefits, large-scale clinical studies are essential, while efforts to enhance accessibility will play crucial role in determining the widespread adoption. Evolution in AR and VR has potential to redefine radiology, eventually bridging the gap between technology and patient-centered care. Both technologies can improve surgical techniques, decrease diagnostic mistakes, and enhance patient outcomes. The research and development in AI integration, user-friendly designs, and affordable solutions can lead to the expansion of their clinical application. The efforts to improve accessibility can lead to wide recognition of these technologies, while vast clinical research is required to confirm their long-term advantages. As AR and VR develop further, they could revolutionize radiology by bringing technology and patient-centered treatment together.